Mucosal 5-aminosalicylic acid concentration inversely correlates with severity of colonic inflammation in patients with ulcerative colitis. Issue 3 (1st September 2000) - Frieri, G; Giacomelli, R; Pimpo, M; Palumbo, G; Passacantando, A; Pantaleoni, G; Caprilli, R
Abstract : BACKGROUND AND AIM: The treatment of ulcerative colitis (UC) with 5-aminosalicylic acid (5-ASA) does not have the same therapeutic effect in all patients. We tested the hypothesis that the effectiveness of the drug is related to its mucosal concentration. PATIENTS: Twenty one UC patients receiving oral 5-ASA (2.4–3.2 g/day) were enrolled in the study. Four were also receiving topical treatment (2 g/day). METHODS: Six endoscopic biopsies were taken from the rectum for measurement of 5-ASA concentrations (ng/mg) by HPLC; soluble interleukin 2 receptor (sIL-2R) concentrations (U/ml) were measured by ELISA and histology. Endoscopic and histological appearance was graded on a four point scale (0–3). The Wilcoxon's rank test and Pearson's correlation coefficient were used for statistical analysis. RESULTS: Mucosal concentrations of 5-ASA were significantly higher (p=0.03) in patients with endoscopic scores of 0–1 compared with those with scores of 2–3 (16.1 (range 10.2–45) v 5.5 (3.5–17.4), respectively) and in patients with lower histological inflammation compared with those with more severe scores (17.4 (10.5–45) v 8.9 (3.5–17.2), respectively) (p<0.01). In contrast, mucosal sIL2-R concentrations were significantly lower in patients with slight endoscopic and histological lesions than in those with more severe disease. A significative inverse correlation ( r =−0.85) was found between 5-ASA and sIL-2R mucosal concentrations (p=0.00008). CONCLUSIONS: In patients with UC, in the same area of the intestinal tract, we found that the higher the 5-ASA mucosal concentrations, the lower the IL-2R levels and endoscopic and histological scores. We hypothesise that maintenance of high mucosal 5-ASA concentrations in all colonic segments could contribute to improve clinical outcome in UC patients.